2020
DOI: 10.37268/mjphm/vol.20/no.1/art.499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Impact Aerobic Dance and Zumba Exercises on Body Fat Percentage in Obese Women

Abstract: The purpose of this study was to examine the effect of low-impact aerobic dance and zumba exercises in reducing the percentage of body fat in obese women in terms of the Body Mass Index (BMI). Forty obese women (mean age 33.9±7.1 years) were selected and divided into two experimental groups, namely: low-impact aerobic dance (n=20) and zumba (n=20). The participants were also divided based on the BMI which gave the mild and severe obesity groups. The research instrument was a skinfold caliper which was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…This whole muscle activity stimulates the muscular tissues and this physiological adaptation to exercises causes hypertrophy of muscles [14] that manifest in decreasing fatty tissues. Aerobic exercises decreases percentage of body fat most significantly [15]. It shows -3.7% decreases on body mass and 2.4% increase in muscle mass upon 12 weeks aerobic exercises intervention [16].The results from this study have confirmed that aerobic exercises training with music at 50-70% intensity of target heart rate given for 3 days a week's led to statistically significant decrease on body fat, these changes may be due to the intensity and frequency of exercises and sincerity of trainees.…”
Section: Discussionmentioning
confidence: 97%
“…This whole muscle activity stimulates the muscular tissues and this physiological adaptation to exercises causes hypertrophy of muscles [14] that manifest in decreasing fatty tissues. Aerobic exercises decreases percentage of body fat most significantly [15]. It shows -3.7% decreases on body mass and 2.4% increase in muscle mass upon 12 weeks aerobic exercises intervention [16].The results from this study have confirmed that aerobic exercises training with music at 50-70% intensity of target heart rate given for 3 days a week's led to statistically significant decrease on body fat, these changes may be due to the intensity and frequency of exercises and sincerity of trainees.…”
Section: Discussionmentioning
confidence: 97%
“…Selain itu latihan senam low-impact dapat mengurangi prosentase lemak tubuh pada wanita gemuk. Senam aerobik low-impact menekankan pembakaran lemak dan perubahan komposisi tubuh sehingga diharapkan dapat menurunkan kelebihan berat badan pada peserta yang obesitas, mengurangi beban pada sendi penopang berat badan dan meingkatkan efektivitas dalam pembakaran lemak tubuh [12]. Menurut hasil penelitian Wiklund, latihan aerobik dengan intensitas sedang selama 6 minggu mampu mengurangi lemak pada wanita dengan kelebihan berat badan dan obesitas, namun keberhasilan dalam menurunkan persentase lemak tubuh dipengaruhi oleh kemampuan peserta dalam melakukan gerakan senam yang terpadu dan harmonis.…”
Section: Hasil Dan Pembahasanunclassified
“…Berdasarkan tabel 2 dapat diketahui bahwa pada tes akhir, berat badan atlet yang berada pada kategori "sangat berat" berjumlah 0 atlet, berada pada kategori "gemuk" berjumlah 3 atlet, berada pada kategoti "ideal" berjumlah 13 atlet, berada pada kategori "kurus" berjumlah 3 atlet, berada pada kategori "sangat ringan" berjumlah 1 atlet. (Octaviana et al, 2020).…”
Section: Metodeunclassified